Physical activity is associated with higher sleep efficiency in the general population: the CoLaus study. Issue 7 (30th March 2018) - Gubelmann, Cédric; Heinzer, Raphael; Haba-Rubio, José; Vollenweider, Peter; Marques-Vidal, Pedro
Abstract: Study Objectives: To evaluate the association of objective physical activity (PA) and sedentary behavior (SB) with sleep duration and quality. Methods: Cross-sectional study including 2649 adults (53.5% women, 45–86 years) from the general population. Proportions of time spent in PA and SB were measured using 14 day accelerometry. Low PA and high SB statuses were defined as the lowest and highest tertile of each behavior. "Inactive, " "Weekend warrior, " and "Regularly active" weekly patterns were also defined. Sleep parameters were derived from the accelerometer and validated questionnaires. Results: High PA, relative to low PA, was associated with higher sleep efficiency (76.6 vs. 73.8%, p < 0.01) and lower likelihood of evening chronotype [relative-risk ratio (RR) and 95% CI: 0.71 (0.52; 0.97)]. Similar associations were found for low SB relative to high SB. "Weekend warriors" relative to "Inactives, " had higher sleep efficiency [76.4 vs. 73.9%, p < 0.01] and lower likelihood of evening chronotype [RR: 0.63 (0.43; 0.93)]. "Regularly actives, " relative to "Inactives, " had higher sleep efficiency [76.7 vs. 73.9%, p < 0.01] and tended to have less frequently an evening chronotype [RR: 0.75 (0.54; 1.04), p = 0.09]. No associations were found for PA and SB with sleep duration, daytime sleepiness, insomnia, and risk of sleep apnea (after adjustment for body mass index). Conclusions: High PA and low SB individuals, even if they do not sleep longer, have higher sleep efficiency and have less frequently an evening chronotype.